Understanding corporate tax avoidance and the causal factors: some evidence from Malaysia - Abdul Khalid, Muhammad Yusof; Turmin, Siti Zaidah; Palil, Mohd Rizal (Human Resource Management Academic Research Society, 2021)
The collection of taxes is vital in contributing towards the revenue of a country. From the perspective of Malaysia, corporate taxes are the largest contributor to the government's revenue. Despite the significant role of corporate taxes in generating revenue for the country, the Malaysian tax authority has faced tax leakages, including tax avoidance. Tax avoidance is a major challenge for Malaysia's tax system, as cases have increased from year to year. This study was conducted to identify the causal factors of tax avoidance by the corporate sector in Malaysia. The sample of the study comprised 260 Malaysian public companies listed on Bursa Malaysia from thirteen economic sectors. The data were analysed using statistical analysis of multiple regression. The study's findings revealed that three company characteristics, namely; total assets, leverage and sales growth, were significant in determining the level of tax avoidance among the companies investigated. This study was fruitful as it has contributed to the knowledge base and tax policymakers in Malaysia.